Synthesis and physicochemical research of some 2-((5-((theophylline-7'-yl)methyl)-4-R-4H-1,2,4-triazole-3-yl)thio)acetohydrazide ylidenderivatives - A. S. Gotsulya; P. S. Knyazevich; O. I. Panasenko; Е. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The rapid development pace of the pharmaceutical science constantly increases the demand for new kind of medicine featured with high biological activity and non-toxicity at the same time. Setting the aim to enlarge the amount of scientific findings in the domain of biologically active substances, 1,2,4-triazole and theophylline were used as the starting material. These compounds form the basis for the majority of drugs, such as diuretics, antifungal and antibacterial medicaments. The combination of heterocycles put under research demonstrate a repeated probability increase in the variety of activities. Therefore, the relevance of the following study is determined by valuable properties of these substances. Besides that, the presence of a hydrazide element accounts for a high probability level of antimicrobial, particularly anti-tuberculosis activity. In order to identify optimal conditions for the synthesis and physicochemical property research, 2-((5-((theophylline-7'-yl)methyl)-4-R-4H-1,2,4-triazole-3-yl)thio) acetohydrazide ylidenderivatives were obtained. The process of production was carried out through long chain reactions, using the sodium salt of theophylline as a substrate. The conversion is well known being described in many papers. Hydrazide was taken as the starting compound. It was dissolved in water-alcoholic medium while separately, aldehyde was dissolved or mixed in ethyl alcohol as well. The resulting solutions were decanted. The precipitate formed immediately or after a certain period of time, which is likely due to the state of matter of the starting aldehyde. 10 compounds (light-yellow crystalline materials with sharp melting point) were synthesized after that. Their structures and physicochemical properties were confirmed with modern methods of analysis. It is established that the reaction proceeds rapidly with a yield of 77‒95% in water-alcoholic medium at a temperature of about 80 °C.